Comparison of the Prescribing Pattern of Bisphosphonate and Raloxifene in Korean Women with Osteoporosis: From a National Health Insurance Claims Database - Kim, Jungmee (PLoS One, 2015)
This study aimed to evaluate the differences of prescribing pattern between bisphosphonate and raloxifene users among Korean women with osteoporosis, focusing on the underlying conditions, concurrent medications, nature of healthcare utilization, and regional disparity. We used the Health Insurance Review and Assessment Service National Patients Sample database of the year 2010. Study subjects were defined as female osteoporosis patients aged over 50 years with both the diagnosis of osteoporosis and prescriptions of bisphosphonate or raloxifene. The frequency and the proportion of bisphosphonate and raloxifene were compared using chi-square test and the trend of the proportion using the Cochran–Armitage test. Medications were quantified as defined daily doses per 1,000 patients per day. The prescription pattern was visualized by using the Quantum Geographic Information Systems program. Of the 1,367,367 people who utilized medical services in 2010, the final number of study subjects was 26,881—26,032 (96.8%) bisphosphonate and 849 (3.2%) raloxifene recipients. Raloxifene users were younger than bisphosphonate users and were more frequently patients with a lipid disorder (16.0% vs. 22.1%, p-value < 0.0001), rheumatic disease (4.0% vs. 6.1%, p-value = 0.0024), hot flash (1.8% vs. 6.1%, p <0.0001), and coronary artery disease (1.2% vs. 2.8%, p< 0.0001). The proportion of raloxifene users was higher in tertiary care institutions (21.6% vs. 44.7%, p-value < 0.0001). A regional distribution showed that raloxifene use was higher in the Seoul metropolitan area. These differences in demographic and clinical profiles of each recipient may influence prescription decisions.